Hell and Its Rivals: Death and Retribution among Christians, Jews, and Muslims in the Early Middle Ages - Bernstein, Alan E. (Cornell University Press, 2017)
Hell and its Rivals -- Contents -- Preface -- Acknowledgments -- List of Abbreviations -- Introduction -- Part I. Foundations -- 1. Gregory the Great: Order in Chaos -- 2. Inner Death: Hell in the Conscience -- 3. The Punishments: Slavery, Torture, and Hell -- Part II. Alternatives to Hell -- 4. Exceptions to Hell: Relief and Escape -- 5. Calibrated Justice and Purgatorial Fire -- 6. Visions: Rights to Souls -- Part III. Hell in Abrahamic Religions -- 7. Rabbinic Judaism: One Fire, Two Fates -- 8. Byzantine Universalism: The Path Not Taken -- 9. Islam: The Mockers Mocked -- Conclusion -- Bibliography -- Index